Refractory Chylothorax in a Patient With Severe Mitral Regurgitation - Sheena Jing Yi Ng; Qiao Li Tan; Ken Junyang Goh; Si Ling Young; Brian Lee Wei Chua; Jane Jing Yi Wong; Ivana Gilcrist Phua; Wen Ting Lim; Carrie Kah‐Lai Leong (Respirology Case Reports)
ABSTRACT We report a case of chylothorax secondary to severe mitral regurgitation, in the absence of heart failure with a low ejection fraction. A 49‐year‐old male presented with mitral valve infective endocarditis, complicated by severe mitral regurgitation with persistent vegetations 5 weeks into treatment. He declined valvular repair. He was admitted four times in the following year for symptomatic right pleural effusion requiring therapeutic chest drainage. Pleural fluid was milky, with elevated triglyceride levels consistent with chylothorax. He underwent mitral valve replacement, with no recurrence of chylothorax to date. The mechanism of chylothorax in mitral regurgitation is likely due to high central venous pressure, with transmitted high right lymphatic duct and thoracic duct pressures. This may then cause reflux of lymph and chyle into pleural lymphatics and subsequent leakage of fluid into the pleural space. This case illustrates mitral regurgitation as a rare cause of chylothorax, with mitral valve replacement granting remission.